1999
DOI: 10.1016/s0969-2126(99)80100-2
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of mammalian purple acid phosphatase

Abstract: Despite less than 15% sequence identity, the protein fold resembles that of the catalytic domain of plant purple acid phosphatase and some serine/threonine protein phosphatases. The active-site regions of the mammalian and plant purple acid phosphatases differ significantly, however. The internal symmetry suggests that the binuclear centre evolved as a result of the combination of mononuclear ancestors. The structure of the mammalian enzyme provides a basis for antiosteoporotic drug design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
236
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(250 citation statements)
references
References 48 publications
14
236
0
Order By: Relevance
“…66 Sequence alignment of RKBPAP with porcine TRAP suggested that RKBPAP is a good model for the structure and mechanism of other acid phosphatases. 67 We recently confirmed this overall prediction with solution of the crystal structure of the porcine enzyme at 1.5 Å resolution 39 (Brookhaven Database, Access Code 1ute). Together with other groups we produced substantial amounts of recombinant mouse, rat, and human TRAP in baculovirus expression systems.…”
Section: Enzyme Mechanism and Conservation Of Trap-like Enzymes From mentioning
confidence: 58%
“…66 Sequence alignment of RKBPAP with porcine TRAP suggested that RKBPAP is a good model for the structure and mechanism of other acid phosphatases. 67 We recently confirmed this overall prediction with solution of the crystal structure of the porcine enzyme at 1.5 Å resolution 39 (Brookhaven Database, Access Code 1ute). Together with other groups we produced substantial amounts of recombinant mouse, rat, and human TRAP in baculovirus expression systems.…”
Section: Enzyme Mechanism and Conservation Of Trap-like Enzymes From mentioning
confidence: 58%
“…We have determined the crystal structure of pig purple acid phosphatase [23] and other groups have solved the structures of the rat enzyme [42,43]. The overall structural features of these mammalian enzymes are very similar, as expected based on the very high degree of sequence identity (>85%) [1].…”
Section: Inhibitor-protein Interactionsmentioning
confidence: 59%
“…The pK es2 value of $6 may correspond to a residue in the active site acting as a general acid to protonate the leaving group on hydrolysis. Residues previously identified as candidates, based on the crystal structures of the pig and red kidney bean enzymes, are the conserved His92 and His195 (pig enzyme numbering), which are within hydrogen bonding distance of bound phosphate [23,32].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Crystal structures have been reported for PAPs isolated from pig uterus, also known as uteroferrin or Uf ( Figure 1) (14), rat bone (15), and red kidney bean (16,17). All PAPs bear an active site comprising a ferric ion (site A) and a divalent metal ion (site B).…”
mentioning
confidence: 99%